Correlation between serum 25-hydroxyvitamin D levels and peripheral neuropathy in type 2 diabetes mellitus - Senzhen Chen; Jinfeng Chen; Shujing Zheng; Yiling Yan; Mengting Huang; Nuoqi Chen (Frontiers in Endocrinology)
ObjectiveTo investigate the correlation between serum 25-hydroxyvitamin D (25[OH]D) levels and diabetic peripheral neuropathy (DPN) in type 2 diabetes mellitus (T2DM) and to evaluate its predictive value for DPN.MethodsParticipants were divided into three groups based on 25(OH)D levels: deficient, insufficient, and normal. The relationship between 25(OH)D and DPN, as well as the correlation of 25(OH)D and DPN with various indicators, was analyzed.ResultsCompared to the non-DPN group (NDPN), the DPN group had significantly lower levels of 25(OH)D3 (22.10 ± 0.77 vs. 24.45 ± 0.66 ng/mL) and total 25(OH)D (23.12 ± 0.74 vs. 25.68 ± 0.67 ng/mL). In addition, significant differences were observed in body mass index (BMI), resting heart rate (RHR), triglyceride (TG), free triiodothyronine (FT3), and blood urea nitrogen (BUN) between the two groups (p < 0.05). Multivariate analysis identified 25(OH)D3, total 25(OH)D, FT3, BMI, and RHR as risk factors for DPN. The receiver operating characteristic (ROC) curve analysis revealed that the optimal cutoff value for 25(OH)D3 in predicting DPN in T2DM was 18.85 ng/mL [area under the curve (AUC) 0.76, 95% confidence interval (CI): 0.697–8.823], while the optimal cutoff for total 25(OH)D was 19.94 ng/mL (AUC 0.765, 95% CI: 0.703–0.828).ConclusionSerum 25(OH)D levels can serve as a simple and effective screening tool to predict the occurrence of DPN in patients with T2DM.